Double‐Patch Repair by a Bilateral Ventriculotomy for Postinfarction Ventricular Septal Defect. Issue 2 (3rd December 2013) - Iwaki, Ryuma; Nakagiri, Keitaro; Murakami, Hirohisa; Morimoto, Naoto; Yoshida, Masato; Mukohara, Nobuhiko
Abstract Objectives Repair of a postinfarction ventricular septal defect (VSD) is a challenging procedure with a high risk of postoperative residual shunt and subsequent mortality. This retrospective study aimed to assess a modified infarct exclusion technique with a biventricular approach. Methods Nineteen consecutive patients who underwent the infarct exclusion procedure for VSD between 2002 and 2011 were reviewed. A biventricular approach (B group: 6 patients) and a left ventricular approach (L group: 13 patients) were studied by univariate analysis. Results The overall 30‐day mortality was 15.8%, and was not different between the two groups (p = 0.94). Postoperative residual shunt was not observed in the B group (p = 0.21). The overall five‐year survival rate was 79%, and there were no late deaths in the B group (p = 0.14). Conclusion The repair of postinfarction VSD can be safely performed by the infarct exclusion technique with a biventricular approach. This technique seems to reduce surgical mortality and prevents recurrence of the VSD. doi: 10.1111/jocs.12262 (J Card Surg 2014;29:181–185)